2012
DOI: 10.1039/c2nr31847d
|View full text |Cite
|
Sign up to set email alerts
|

Graphene nanoribbon-guided fluid channel: a fast transporter of nanofluids

Abstract: In this work, we present a conceptual design of nanofluid channels using graphene sheets as the container and nanoribbons as flow guiders. Using molecular dynamics simulations, we demonstrate that water molecules confined in such nanochannels can be well guided by the nanoribbons and form a regular shaped water stream. The viscosity of water transported along such nanochannels is found to be orders of magnitude lower than that of bulk water. Several unconventional structural and flow characteristics are reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…These three quantities are closely correlated11429. The effective shear force can be estimated as τ  =  Nma / S , where N is the total number of water molecules inside the channel, m the atomic mass of a water molecule, and S the contacting area between water and the GE wall.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These three quantities are closely correlated11429. The effective shear force can be estimated as τ  =  Nma / S , where N is the total number of water molecules inside the channel, m the atomic mass of a water molecule, and S the contacting area between water and the GE wall.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that when confined in nanochannels with sizes ranging from sub-nanometer to several nanometers, fluids can exercise unconventional and sometimes even counterintuitive behaviors121314151617. Such behaviors are mainly due to the fact that the interactions among the fluid ions or molecules change dramatically when they are in close contact with the confining walls1518.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our proposed mechanism can be feasibly extended to design other potential directional motion actuation scheme. For example, two graphene planes forming a channel has been proposed as nanofluid channels [45][46][47][48]. As a simple demonstration for such application, we show that strain engineered graphene nanochannel can offer intrinsic actuation force that can potentially pump the molecules moving from one end of the channel to another.…”
Section: Concluding Remarks On Strain Gradient Induced Actuation and mentioning
confidence: 97%
“…In the experiments on the 2D nanoslits, the driving pressure is only one third of that in 1D nanotubes and the conduction plateau becomes flat fast. Compared with the axial constraints of 1D nanotubes, 2D nanoslits [44] or nanoribbons [45] relaxed the constraints from the lateral directions on the confined water molecules, and the additional degree of freedom allowed the confined water molecules to reach a lower system free energy, promoting the formation of more energetically favourable molecular configurations with little interlayer resistance in 2D nanoenvironments.…”
Section: Fluidic Behaviours In Fgamentioning
confidence: 99%